Dongeng Aceh: Pangeran Amat Mude dalam Animasi 2 Dimensi (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
Nanggroe Aceh Darussalam is one of the provinces in Indonesia, which has a rich cultural heritage. One of them is folk tales. After conducting the research, In these days the story of Aceh has slowly not recognized even by the people of Aceh itself. If we continue to ignore this case, Aceh's tale might be forgotten slowly. Regarding to that case, this 2D Animation work created by purposed to perpetuate and to increase the number of awareness current generation of our local fables. Also, the media that used in this work was based on current trends. This work visualised by 2D Animation video with the title of work called